2014
DOI: 10.4321/s0213-61632014000400002
|View full text |Cite
|
Sign up to set email alerts
|

Lower risk of prostate cancer in schizophrenia: fact or artifact?

Abstract: -Background and Objectives: Reduced risk for prostate cancer in persons diagnosed with schizophrenia has been reported repeatedly. While genetic factors and antipsychotic medications were imputed, a methodological hypothesis could be raised: given the reported disparities of health services with regard to service users with schizophrenia these persons may be screened less often compared to schizophrenia-free counterparts resulting in undetected prostate tumors. The study objective was to compare the rates of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For instance, increased cancer mortality in mental illness may be due to disparities in care (13), in that people with mental illness are significantly less likely to receive surgical interventions or radiotherapy and to have fewer chemotherapy sessions (10). Additionally, it has been suggested that those with mental illness may be less tolerant of intensive treatment regimens with significant side effect burdens and also that comorbid physical illness may contribute to the increased mortality rates (14).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, increased cancer mortality in mental illness may be due to disparities in care (13), in that people with mental illness are significantly less likely to receive surgical interventions or radiotherapy and to have fewer chemotherapy sessions (10). Additionally, it has been suggested that those with mental illness may be less tolerant of intensive treatment regimens with significant side effect burdens and also that comorbid physical illness may contribute to the increased mortality rates (14).…”
Section: Introductionmentioning
confidence: 99%